KETERATURAN KUNJUNGAN ANC BERHUBUNGAN DENGAN PARITAS PADA IBU HAMIL TRIMESTER AKHIR - suparni, ita (STIKES dan AKZI Karya Husada Kediri, 2024)
Antenatal Care (ANC) is the most important component of maternal health services to reduce maternal and infant mortality. The regularity of ANC can be shown through the frequency of visits, it turns out this is a problem because not all pregnant women check their pregnancies regularly so abnormalities arising in pregnancy cannot be detected as early as possible. The purpose of the study was to determine the relationship between parity and the regularity of ANC visits in third-trimester pregnant women in Sumari Duduksampeyan Village, Gresik Regency. The research design is correlational analytics with a cross-sectional approach. The population is all third-trimester pregnant women in Sumari Dudukansampeyan Village as many as 45 respondents in July 2023. A sample of 36 respondents. The sampling technique uses simple random sampling. Parity independent variable. The dependent variable is the regularity of ANC visits. Research instruments with questionnaires and books on maternal and child health. Analysis with Spearman's Rho. The results of the analysis were obtained from 36 respondents who had complete basic immunization status and as many as 25 respondents who were regularly in ANS examinations, of which 18 respondents (50%) were primipara, The results of Spearman's Rho show that the significance value (Sig. 2-tailed) for this correlation is 0.001, so it can be concluded that there is a relationship between parity and the regularity of ANC visits to third trimester pregnant women in Sumari Duduksampeyan Village, Gresik Regency. It is hoped that health workers can play an active role in providing education to the public by providing information, especially about the regularity of antenatal care examinations for pregnant women.